Factors associated with secretory IgA levels in colostrum and breastmilk - Sri Priyantini Mulyani; Suprihati Winarto; Hesti Wahyuningsih Karyadini (Indonesian Pediatric Society, 2023)
Background Secretory IgA (sIgA) content of breastmilk in the first postpartum month is a reflection of the pregnant woman's immune response to environmental antigen exposure. The role of secretory IgA in breastmilk is to protect and support the development of the neonatal immune response in early life. Objective To examine possible factors associated with sIgA levels in breastmilk and colostrum, including environmental exposure, food consumed, maternal history of atopy, and the appearance of allergic symptoms in infants. As a secondary objective, we determined the association between infant factors (IgE, exposure to cigarette smoke) and maternal factors (sIgA, maternal allergies) with infant allergies. Methods This prospective cohort study of 80 postpartum mothers and their infants was conducted at Sultan Agung Islamic Hospital, Semarang. We collected maternal colostrum on the second or third postpartum day and mature milk between the 22nd to 25th postpartum day. Exposure factors to mothers and infants in the final trimester of pregnancy up to one month postpartum was recorded through a questionnaire and home visits. The infant’s IgE level was measured at 4 months of age. Results Mean colostrum sIgA was 108.9 (SD 16.5) mg/dL (95%CI 97.9 to 121.1 mg/dL) and mean mature milk sIgA was 94.1 (SD 23.9) mg/dL (95%CI 89.1 to 99.2 mg/dL). Mean colostrum sIgA levels were higher in mothers exposed to cigarette smoke [119.1 (SD 1.7) vs. 92.9 (SD 1.5) mg/dL; P=0.026] and frequent infections [128.2 (SD 1.7) vs. 95.9 (SD 1.6) mg/dL; P=0.007] compared to that in unexposed mothers. Mean colostrum sIgA was also higher in mothers with atopic allergy than in those without (136.8 mg/dL vs. 99.3 mg/dL; p=0.017) and in mothers of infants with IgE levels >29 IU/ml than in mothers of infants with IgE levels <29 IU/mL (136.8 vs. 101.2 mg/mg/dL; P=0.045). Elevated colostrum sIgA (>136.8 mg/dL) was not associated with allergies in the infants (P=0.269). Conclusions Maternal atopic allergy and frequent infections are associated with increased colostrum sIgA levels. Breastmilk sIgA levels are not associated with allergies in the infant. Maternal exposure to antigens may stimulate the production of specific breastmilk sIgA.